La Geología, vista desde la Filosofía - Camacho, Luis (2011)
Philosophy of science took physics as the model for all sciences, at the expense of other sciences like geology. Immune from criticism and forgotten by both critics and defenders of scientific theories and institutions, geology enjoys a peculiar position which in fact has been an obstacle for a philosophical discussion on object, methods and types of reasoning. A failed prediction of an earthquake in Costa Rica is taken as an example of an issue worth analyzing.